A comparative biomechanical study of repaired tendons wrapped with two biological matrices in Bucks: ¹Department of Surgery and Obstetrics, College of Veterinary Medicine, Baghdad University, ²Directorates of Materials Research in Ministry of Science and Technology, Baghdad, Iraq. - AL-Falahi, N. H. (The Iraqi Journal of Veterinary Medicine, 2016)
This study is planned to evaluate the efficacy of two biological matrices represented by autologous platelet rich fibrin matrix, as well as a cross linked decellularized caprine pericardial extracellular matrix on enhancing healing of the experimentally severed superficial digital flexor tendon in a goat model. It was carried out on 48 adult apparently healthy bucks, which were divided randomly into three equal groups. Under the effect of sedative and local ring block anesthesia, superficial digital flexor tendon was severed at the mid metacarpal region of the right forelimb. In the first control group, tenorrhaphy was performed and left without additives. While in the second group the tenorrhaphy site was wrapped with a previously prepared autologous platelet rich fibrin strips, as well as in the third group the tenorrhaphy site was wrapped with a cross linked decellularized pericardial extracellular matrix strip which was prepared from the whole fresh caprine pericardium obtained from the slaughter house. Both matrices were fixed in their position at the tenorrhaphy site by few interrupted stitches. The biomechanical evaluation of the operated tendon indicated an increase in tensile strength with time in all groups, but the comparisons among groups showed a significant (P≤0.05) increase at day 15 in both treated as compared to control animals. On day 45 the pericardial extracellular matrix group showed a significant increase in tensile strength as compared to platelet rich fibrin matrix and control groups, but at day 75 there were no differences among groups, at day 180 the pericardial extracellular matrix group showed a significant increase in the tensile strength as compared to platelet rich fibrin matrix and control groups. In conclusion, both biological matrices led to improvement in the biomechanical properties of the operated tendons with time.